THE EFFECTIVENESS OF DICTOGLOSS IN TEACHING WRITING SKILL VIEWED FROM STUDENTS' MOTIVATION - dian pertiwi (IJET (Indonesian Journal of English Teaching), 2018)
This article refers to an experimental study on the effectiveness of Dictogloss to teach writing skill at one of Islamic School in Surakarta. The sampling used in this research was cluster random sampling with two classes as sample, namely experimental class taught using Dictogloss and control class taught using Direct Instruction. The collect the data, there were two instruments used in this research namely, writing test and motivation questionnaire. Writing test was used to find out students’ writing skill, while motivation questionnaire was conducted to know students’ motivation levels. The data were analyzed by using 2x2 Multifactor Analysis of Variance (ANOVA). Before conducting the ANOVA test, pre-requisite test namely normality and homogeneity test were conducted. The result of this research shows that: (1) Dictogloss is more effective than Direct Instruction to teach writing; (2) Students having high motivation have better writing skill than those having low motivation.